Consumer Perceptions, Understanding and Use of Product Related Environmental Information : A literature review of the Nordic knowledge base (Copenhagen : Nordic Council of Ministers, 2004)
Product related environmental information is considered to be an important policy instrument for the support of a shift towards more sustainable consumption patterns. Such information aims to guide consumers to choose environmentally improved products in purchase situations. While eco-labelling has had a particularly strong breakthrough in Nordic markets, a number of other communication modes, such as environmental product declarations and producers’ self-declared claims have been applied, in both the consumer and business-to-business markets. Furthermore, product related environmental information is meant to promote consumer awareness about products’ environment performance. However, to stimulate the desired market transition, consumers need to actually take producers information into account.This report comprises a summary of recent research on how Nordic consumers perceive, understand and use product related environmental information. A comprehensive literature review supplemented with expert interviews forms the foundation for this work. The report highlights well-researched areas and proposes areas where deeper knowledge and understanding is required. The research was conducted cooperatively between IIIEE at Lund University in Sweden, the National Consumer Research Centre in Finland, and Environice in Iceland with the purpose to obtain and present a comprehensive picture of the situation in the Nordic countries.